Functional Analysis of the NucS/EndoMS of the Hyperthermophilic Archaeon Sulfolobus islandicus REY15A - Ahmad, Sohail; Huang, Qihong; Ni, Jinfeng; Xiao, Yuanxi; Yang, Yunfeng; Shen, Yulong (Frontiers in Microbiology, 2020)
EndoMS is a recently identified mismatch specific endonuclease in Thermococcales of Archaea and Mycobacteria of Bacteria. The homologs of EndoMS are conserved in archaea and actinobacteria, where the classic MutS-MutL mediated DNA mismatch repair pathway is absent or non-functional. Here, we report the in vitro mismatch cleavage activity and in vivo function of the EndoMS homolog (SisEndoMS) from Sulfolobus islandicus REY15A, the model archaeon belonging to Crenarchaeota. SisEndoMS is highly active on duplex DNA containing G/T, G/G, and T/T mismatches. Interestingly, the cleavage activity of SisEndoMS is stimulated by the heterotrimeric PCNAs, and when Mn2+ was used as the co-factor instead of Mg2+, SisEndoMS was also active on DNA substrates containing C/T or A/G mismatches, suggesting that the endonuclease activity can be regulated by ion co-factors and accessory protein. We compared the spontaneous mutation rate of the wild type strain REY15A and delta endoMS by counter selection against 5-fluoroorotic acid (5-FOA). The endoMS knockout mutant had much higher spontaneous mutation rate (5.06×10-3) than that of the wild type (4.6×10-6). A mutation accumulation analysis also showed that the deletion mutant had a higher mutation occurrence than the wild type, with the transition mutation being the dominant, suggesting that SisEndoMS is responsible for mutation avoidance in the hyperthermophile. Overexpression of the wild type SisEndoMS in S. islandicus resulted in retarded growth and abnormal cell morphology, similar to strains overexpressing Hje and Hjc, the Holliday junction endonucleases. Transcriptomic analysis revealed that SisEndoMS overexpression led to upregulation of distinct sets of genes including the CRISPR-Cas IIIB system, methytransferases, and glycosyltransferases, which are mainly localized to a specific segment in the chromosome. Collectively, our results support that EndoMS proteins represent a noncanonical DNA repair pathway in archaea. The mechanism of this mismatch repair pathway is discussed.